Certificação ambiental no ramo automotivo: uma proposta de um “selo verde” para concessionárias e oficinas com base em indicadores ambientais - Araújo, Laiz Hérida Siqueira de (2018)
The car dealerships and automobile repair shops have looked for different alternatives to attend the requirements of the regulatory agencies and its own market. However, getting an environmental certification is something far from the reality of micro and small business. Under the circumstances, the present work aimed to develop a new methodology of environmental certification to car dealerships and automobile repair shops based on the data collection of environmental indicators and its weightings. The step s taken in order to achieve this goal were, sequentially: the mapping of zones, activities and actions; the identification of environmental aspects and impacts; the definition of indicators to be used on the certification process and its weighting; the pro position of a method of evaluation; and, finally, the elaboration of a general rules of procedures, as well as a normative regulation to the certification. Throughout the identification of operational zones, activities and actions, as well as the mass bala nce in order to specify the entries and exits of the processes, it was possible to identify 15 aspects, which generated 10 types of environmental impacts. There were defined 94 indicators, in which 24 were considered in the bronze level (legal requirements ), 54 were considered in the silver level (environmental management) and 16 were considered in the gold level (continuous improvement). Thus, the indicators were classified into 3 classes of significance, all with their respective importance. Besides, afte r the application of all indicators into the Classifying Weighting Equation ( Equação de Ponderação Classificatória ) developed in this thesis, it was generated the Sustainability Index ( Índice de Sustentabilidade ) – in which 8.0 or plus stands for bronze l evel, 8.5 stands for silver level, and 9.0 stands for gold level. Therefore, it was found that the adoption of an environmental certification to car dealerships and automobile repair shops is possible and necessary through the methodology proposed by this work. It is believed that it will become doubly successful once it provides a tool to the building trust relationship between the end user and regulatory agencies to the certified companies. So, the certified companies are highlighted not only through gett ing a “Green Seal”, but also through the application of a method that matches their own financial situation